Chemically Reduced Graphene Oxide for the Assessment of Food Quality: How the Electrochemical Platform Should Be Tailored to the Application. Issue 8 (12th January 2017) - Chng, Chu'Er; Ambrosi, Adriano; Chua, Chun Kiang; Pumera, Martin; Bonanni, Alessandra
Abstract: Graphene platforms have been drawing considerable attention in electrochemistry for the detection of various electroactive probes. Depending on the chemical composition and properties of the probe, graphene materials with diverse structural features may be required to achieve an optimal electrochemical performance. This work comprises a comparative study on three chemically modified graphenes, obtained from the same starting material and with different oxygen functionalities and structural defects (graphene oxide (GO), chemically reduced graphene oxide (CRGO), and thermally reduced graphene oxide (TRGO)) towards the electrochemical detection of quinine, an important flavoring agent present in tonic‐based beverages. In general, the reduced graphenes, namely CRGO and TRGO, showed enhanced performance in terms of calibration sensitivity and selectivity, due to the improved heterogeneous electron‐transfer rates on their surfaces. In particular, CRGO provided the best overall electrochemical performance, which can be attributed to its higher density of structural defects and reduced amount of oxygen functionalities. For this reason, CRGO was employed for the electrochemical detection of quinine in commercial tonic drink samples, showing high sensitivity and selectivity, and therefore representing a valid low‐cost alternative to more complicated and time consuming traditional analytical methods. Abstract : Just the tonic : Chemical and thermal reduction of graphene produces materials with enhanced electrochemical properties. These materials have been investigated for their potential application in the detection of quinine concentration in food and drink products, as a simple, low‐cost alternative to traditional lab analysis.